2020
DOI: 10.1002/jbm4.10349
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Cyclic Loading During Adolescence Improves Tibial Bone Microstructure and Strength at Adulthood

Abstract: Bone is a unique living tissue, which responds to the mechanical stimuli regularly imposed on it. Adolescence facilitates a favorable condition for the skeleton that enables the exercise to positively influence bone architecture and overall strength. However, it is still dubious for how long the skeletal benefits gained in adolescence is preserved at adulthood. The current study aims to use a rat model to investigate the effects of in vivo low‐ (LI), medium‐ (MI), and high‐ (HI) intensity cyclic loadings appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 101 publications
(220 reference statements)
0
1
0
Order By: Relevance
“…46 Similarly, increases in bone mineral density, bone volume fraction, trabecular bone thickness, trabecular number, and decreased trabecular spacing were observed after 1250 με at 2 Hz was applied in vivo to rat tibiae for eight weeks. 47 However, at a nonstress-normalized intermittent cyclic load of 17 N at 2 Hz applied for 10 min/day to adolescent rat ulnae, mineralization was arrested completely, and furthermore partially suppressed at 8.5 and 4 N loads applied in a similar manner. 18 One possibly contra-indicating study by Niehoff et al 20 reported that adolescent rats allowed unlimited exercise showed increased osteonectin in the hypertrophic zone relative to limited or no exercise groups, which correlates to promotion of ossification.…”
Section: Matrix Mineralizationmentioning
confidence: 90%
“…46 Similarly, increases in bone mineral density, bone volume fraction, trabecular bone thickness, trabecular number, and decreased trabecular spacing were observed after 1250 με at 2 Hz was applied in vivo to rat tibiae for eight weeks. 47 However, at a nonstress-normalized intermittent cyclic load of 17 N at 2 Hz applied for 10 min/day to adolescent rat ulnae, mineralization was arrested completely, and furthermore partially suppressed at 8.5 and 4 N loads applied in a similar manner. 18 One possibly contra-indicating study by Niehoff et al 20 reported that adolescent rats allowed unlimited exercise showed increased osteonectin in the hypertrophic zone relative to limited or no exercise groups, which correlates to promotion of ossification.…”
Section: Matrix Mineralizationmentioning
confidence: 90%